Reading the (not so) loose ends of multifarious stories: Burman, E, Aitken, G, Alldred, P, Allwood, R, Billington, T, Goldberg, 8, Gordo Lopez, A J, Heenan, C, Marks, D & Warner, S (1996) Psychology discourse practice: From regulation to resistance. London. Taylor & Francis. ISBN 0-7484-0504-6 pbk. 232 pages. - Wilbraham, Lindy (PINS-Psychology in Society, 2026)
Psychology discourse practice is about the role of psychology as social practices which shape and govern our lives, and deploys a (mostly) Foucauldian analysis of "the psy complex" in contemporary western societies, where a proliferation of psychological discourses construct "individuals" with enduring personalities, rights, responsibilities, sexualities, etc. (cf. Rose, 1985). In a critical frame, this is a reading of how psychology functions within current institutionalized structures of inequality (eg. gender, "race", class, age, sexuality, disability), to produce experienced conditions of oppression, exclusion, pathologization and normalization. While psychological professionals labour as gatekeepers who police ab/normality, more implicit regulation operates through seepage of psychological ideas into popular cultural forms, enabling us to experience our lives in these terms.